2021
DOI: 10.3390/ijms22168914
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 6 Is Colocalized and Interacts with Mutant Huntingtin in Huntington Disease Rodent Animal Models

Abstract: Mammalian transglutaminases (TGs) catalyze calcium-dependent irreversible posttranslational modifications of proteins and their enzymatic activities contribute to the pathogenesis of several human neurodegenerative diseases. Although different transglutaminases are found in many different tissues, the TG6 isoform is mostly expressed in the CNS. The present study was embarked on/undertaken to investigate expression, distribution and activity of transglutaminases in Huntington disease transgenic rodent models, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 89 publications
0
4
0
1
Order By: Relevance
“…Mutation, CNV and DNA methylation analysis of TG family members TG mutations have been demonstrated to related to various diseases (20,(39)(40)(41). Mutations of TG family genes were also identi ed in TCGA cohort (Fig.…”
Section: Results Expression Patterns and Clinical Relevances Of Tgs I...mentioning
confidence: 88%
“…Mutation, CNV and DNA methylation analysis of TG family members TG mutations have been demonstrated to related to various diseases (20,(39)(40)(41). Mutations of TG family genes were also identi ed in TCGA cohort (Fig.…”
Section: Results Expression Patterns and Clinical Relevances Of Tgs I...mentioning
confidence: 88%
“…Mutation, CNV and DNA methylation analysis of TG family members TG mutations have been demonstrated to related to various diseases (20,(39)(40)(41). Mutations of TG family genes were also identi ed in TCGA cohort (Fig.…”
Section: Results Expression Patterns and Clinical Relevances Of Tgs I...mentioning
confidence: 90%
“…Moreover, studies in cellular and drosophila models have shown that TG2 acts as a selective corepressor of the nuclear genes involved in HD, whereas the inhibition of its activity or the prevention of its translocation to the nucleus fails to repress transcription [97]. In addition to TG2, TG6 physically interacts with mHTT and contributes to mHTT aggregates in HD transgenic animals, highlighting the role of TG6 activity in the pathogenesis of HD [168].…”
Section: Tg2 In Huntington's Diseasementioning
confidence: 99%